Poznavanje demence med mladostniki v starajoči se družbi - Felc, Zlata (Teorija in praksa, 2020)
Since they are no longer able to take care of themselves, many persons with dementia move to live in with intergenerational families that include their adult children and adolescent grandchildren. The purpose of this research was to find out whether adolescents are familiar with dementia, with a focus on the comparison between genders, and between those with/ without relatives with dementia. A survey of 70 respondents among eighth-graders and high schoolers in the Savinja Statistical Region in Slovenia was used. Future research could help them better understand that forgetfulness isn't normal part of ageing and lead to strategies to improve what adolescents know about dementia.
Keywords: Demenca; Dementia; Mladina; Population aging; Staranje prebivalstva; Youth